Hot-dip plated steel sheet

By adjusting the chemical composition and surface configuration of the hot-dip plating layer, the text or design of the hot-dip plating steel plate is shown, which solves the problem of difficulty in taking into account both durability and corrosion resistance in the prior art, and achieves efficient pattern display and coating performance.

CN119301294APending Publication Date: 2025-01-10NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380043997.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The prior art is difficult to display text or design on the surface of hot-dip plated steel plates to maintain durability and corrosion resistance, and printing or coating processes increase costs and time, and inks may reduce corrosion resistance of the coating.

Method used

By adjusting the chemical composition of the hot-dip plating layer, including the content of Al and Mg, and hot-dip plating is arranged on the surface of the steel plate with low cleanliness, the patterned part and non-patterned part are formed, and the regions are divided by imaginary lattice lines to control the Zn phase The distribution of Al/MgZn2/Zn ternary eutectic structures shows text or design without affecting the corrosion resistance of the plating.

Benefits of technology

It achieves excellent durability and corrosion resistance of text or design on the surface of hot-dip plated steel plate, avoids the increase in cost and time of printing or coating processes, and maintains the corrosion resistance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301294A_ABST
    Figure CN119301294A_ABST
Patent Text Reader

Abstract

The hot-dip plated steel sheet is provided with a hot-dip plating layer formed on the surface of the steel sheet, a pattern portion and a non-pattern portion are formed in the hot-dip plating layer, the pattern portion and the non-pattern portion include a first region and a second region defined below, and the absolute value of the difference in the area ratio of the first region between the pattern portion and the non-pattern portion is 30% or more. A cross-section parallel to the surface of the hot-dip plating layer is exposed at a position of 3t / 4, t / 2, or t / 4 from the surface of the hot-dip plating layer, and a virtual grid line is drawn in each cross-section. A region in which the ratio of the area fraction B of the (Zn phase) to the total area fraction A of the (Zn phase) and the (Al / MgZn2 / Zn ternary eutectic structure) is 20% or more is defined as a first region, and a region in which the ratio is less than 20% is defined as a second region.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to hot-dip coated steel sheets.

[0002] This application claims priority based on Japanese Patent Application No. 2022-094358 filed in Japan on June 10, 2022, and the contents are incorporated herein by reference. Background Art

[0003] Hot-dip plated steel sheets have excellent corrosion resistance, and Zn-Al-Mg hot-dip plated steel sheets have particularly excellent corrosion resistance. Such hot-dip plated steel sheets are widely used in various manufacturing industries such as building materials, home appliances, and automobiles, and their usage has been increasing in recent years.

[0004] However, in order to express characters, designs, etc. on the surface of the hot-dip coating layer of the hot-dip coated steel sheet, characters, designs, etc. may be expressed on the surface of the hot-dip coating layer by subjecting the hot-dip coating layer to a process such as printing or painting.

[0005] However, if the hot-dip coating is subjected to processes such as printing or coating, there is a problem of increased cost and time for applying text or design. Furthermore, when the surface of the coating is made to show text, design, etc. by printing or coating, not only does the metallic gloss appearance, which is highly supported by the demanders, disappear, but also due to the problem of time-dependent degradation of the coating film itself and the time-dependent degradation of the adhesion of the coating film, the durability is poor, and the text, design, etc. may disappear over time. In addition, when the surface of the coating is made to show text, design, etc. by printing ink, although the cost and time can be relatively suppressed, there is a concern that the corrosion resistance of the hot-dip coating will be reduced due to the ink.

[0006] As shown in the following patent documents, various technologies have been developed for Zn-Al-Mg hot-dip plated steel sheets, but there is no known technology for improving the durability when letters, designs, etc. are expressed on the surface of the plated layer.

[0007] Regarding Zn—Al—Mg based hot dip plated steel sheets, there is a conventional technology which aims to make the pear-skin-like plating appearance seen on the Zn—Al—Mg based hot dip plated steel sheets more beautiful.

[0008] For example, Patent Document 1 describes a Zn-Al-Mg hot-dip plated steel sheet having a fine texture and smooth pear-skin appearance with many glossy parts, that is, a good pear-skin appearance with many white parts per unit area and a large proportion of the area of ​​the glossy parts. In addition, Patent Document 1 describes that the unpreferable pear-skin state is a state showing a surface appearance in which amorphous white parts and round glossy parts are mixed and scattered on the surface.

[0009] In addition, Patent Document 2 describes a Zn-Al-Mg based plated steel sheet, which improves the appearance of the plating by making the portion in the thickness direction cross section of the plating layer where no Al crystals exist between the interface between the plating layer and the base metal and the plating surface layer account for 10% to 50% of the width direction length of the cross section.

[0010] Furthermore, Patent Document 3 describes a hot-dip galvanized steel sheet with excellent formability, wherein the center line average roughness Ra of the plated steel sheet surface is 0.5 to 1.5 μm, the PPI (the number of peaks with a size of 1.27 μm or more contained in every 1 inch (2.54 cm)) is 150 to 300, and the Pc (the number of peaks with a size of 0.5 μm or more contained in every 1 cm) is Pc ≥ PPI / 2.54+10.

[0011] In addition, Patent Document 4 describes a highly corrosion-resistant hot-dip galvanized steel sheet in which the glossiness of the entire coating layer is increased and the uniformity of the appearance is improved by refining the ternary eutectic structure of Al / MgZn2 / Zn.

[0012] However, when characters or the like are displayed on the surface of a plating layer, a technique for improving the durability thereof without reducing the corrosion resistance has not been known in the past.

[0013] Prior art literature

[0014] Patent Literature

[0015] Patent Document 1: Japanese Patent No. 5043234

[0016] Patent Document 2: Japanese Patent No. 5141899

[0017] Patent Document 3: Japanese Patent No. 3600804

[0018] Patent Document 4: International Publication No. 2013 / 002358 Summary of the invention

[0019] Problems to be solved by the invention

[0020] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a hot-dip plated steel sheet which can express characters, designs, etc. on the surface of the plated layer and has excellent durability and excellent corrosion resistance.

[0021] Means for solving problems

[0022] The gist of the present invention is as follows.

[0023] [1] A hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet,

[0024] The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities, as an average composition.

[0025] The hot-dip galvanized layer has a pattern portion and a non-pattern portion.

[0026] The pattern portion and the non-pattern portion each include one or two of the first region and the second region obtained by the following measurement method,

[0027] An absolute value of a difference between an area ratio of the first region in the pattern portion and an area ratio of the first region in the non-pattern portion is 30% or more.

[0028] [Measurement method]

[0029] The thickness of the hot-dip galvanized layer is set to t, and a square cross section of 1 to 5 mm parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position away from the surface of the hot-dip galvanized layer. In each of the above cross sections, imaginary grid lines are drawn at intervals of 0.5 mm. In the multiple regions divided by the above imaginary grid lines, the region where the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more is set as the above-mentioned first region, and the region where the ratio (B / A (%)) is less than 20% is set as the second region.

[0030] [2] A hot-dip plated steel sheet comprising a steel sheet and a hot-dip plated layer formed on a surface of the steel sheet,

[0031] The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities, as an average composition.

[0032] further comprising one or two selected from the following Group A and Group B,

[0033] The hot-dip galvanized layer has a pattern portion and a non-pattern portion.

[0034] The pattern portion and the non-pattern portion each include one or two of the first region and the second region obtained by the following measurement method,

[0035] An absolute value of a difference between an area ratio of the first region in the pattern portion and an area ratio of the first region in the non-pattern portion is 30% or more.

[0036] [Group A] Si: 0.0001 to 2 mass%

[0037] [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2% by mass in total

[0038] [Measurement method]

[0039] The thickness of the hot-dip galvanized layer is set to t, and a square cross section of 1 to 5 mm parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position away from the surface of the hot-dip galvanized layer. In each of the above cross sections, imaginary grid lines are drawn at intervals of 0.5 mm. In the multiple regions divided by the above imaginary grid lines, the region where the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more is set as the above-mentioned first region, and the region where the ratio (B / A (%)) is less than 20% is set as the second region.

[0040] [3] The hot-dip coated steel sheet according to [1] or [2], characterized in that the pattern portion is arranged in a shape that becomes any one of a straight line portion, a curved line portion, a dot portion, a figure, a number, a symbol or a character, or a combination of two or more of them.

[0041] [4] The hot-dip coated steel sheet according to any one of [1] to [3], wherein the coating weight of the hot-dip coating layer on both sides of the steel sheet is 30 to 600 g / m 2 .

[0042] [5] The hot-dip plated steel sheet according to any one of [2] to [4], wherein the hot-dip plated layer has an average composition containing the group A in mass %.

[0043] [6] The hot-dip plated steel sheet according to any one of [2] to [5], wherein the hot-dip plated layer has an average composition containing the group B in mass %.

[0044] Effects of the Invention

[0045] According to the present invention, it is possible to provide a hot-dip plated steel sheet in which characters, designs, etc. can be expressed on the surface of the hot-dip plated layer and which has excellent durability and corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 It is a schematic cross-sectional view for explaining a cross section (exposed surface) for measuring the coating structure of the hot-dip coating layer in the Zn—Al—Mg-based hot-dip coated steel sheet as an embodiment of the present invention.

[0047] Figure 2 It is a perspective view for explaining an exposed surface for measuring the coating structure of the hot-dip coating layer in a Zn—Al—Mg-based hot-dip coated steel sheet as an embodiment of the present invention.

[0048] Figure 3 It is a schematic diagram of the first region and the second region of the Zn—Al—Mg-based hot-dip plated steel sheet as an embodiment of the present invention.

[0049] Figure 4 This is a schematic diagram of a metal plate having a lattice shape used to transfer Zn powder to the surface of a steel plate in an example. DETAILED DESCRIPTION

[0050] The inventors of the present invention conducted a detailed investigation on the coating of a Zn-Al-Mg hot-dip plated steel sheet showing a pear-skin-like appearance. The pear-skin-like appearance is manifested by the presence of a fine metallic luster portion showing a metallic luster and a fine white portion showing a white color mixed together. The structure of the coating at the metallic luster portion was investigated, and it was found that the area fraction of the [Zn phase] in the coating surface was reduced compared with the white portion. On the other hand, the structure of the coating at the white portion was investigated, and it was found that the ratio of the [Zn phase] to the [ternary eutectic structure of Al / MgZn2 / Zn] was higher than that of the metallic luster portion.

[0051] Therefore, a study was conducted to determine whether the distribution state of the metallic glossy portion and the white portion in the hot-dip coating can be arbitrarily controlled. As a result, it was found that by adjusting the chemical composition of the hot-dip coating and configuring an area with relatively low cleanliness on the surface of the steel plate in an intentional shape before immersing the steel plate in the hot-dip coating bath, and then performing hot-dip coating, an area containing relatively more metallic glossy portions can be intentionally configured on the surface of the hot-dip coating, thereby completing the present invention.

[0052] Hereinafter, a hot-dip plated steel sheet as an embodiment of the present invention will be described.

[0053] The hot-dip galvanized steel sheet of this embodiment is Figure 1 to Figure 3 As shown in the figure, it comprises a steel plate 1 and a hot-dip galvanized layer 2 formed on the surface of the steel plate 1, the hot-dip galvanized layer 2 contains Al: 5-22 mass %, Mg: 1-10 mass %, and the remainder contains Zn and impurities in terms of average composition, the hot-dip galvanized layer 2 has a pattern portion 21 and a non-pattern portion 22, the pattern portion 21 and the non-pattern portion 22 respectively contain one or two of a first region A1 and a second region A2 obtained by the following measuring method, and the absolute value of the difference between the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22 is greater than 30%.

[0054] The area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22 are measured as follows. The thickness of the hot-dip galvanized layer 2 is set to t, and a 1 to 5 mm square cross section parallel to the surface 2a of the hot-dip galvanized layer 2 is exposed at any position of 3t / 4, t / 2 or t / 4 from the surface of the hot-dip galvanized layer 2. Then, as Figure 3 As shown in the example, imaginary grid lines are drawn at intervals of 0.5 mm in each cross section, and in the multiple regions divided by the imaginary grid lines, the region where the ratio (B / A(%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is greater than 20% is set as the first region A1, and the region where the ratio (B / A(%)) is less than 20% is set as the second region A2.

[0055] It should be noted that Figure 3 The exposed surface for measurement illustrated in the example is a square of 5 mm square. In this exposed surface, the number of areas divided by imaginary grid lines is 100. In the case where the pattern portion is small and an exposed surface of 5 mm square cannot be formed inside the pattern portion, the size of the exposed surface can also be reduced. In this case, a plurality of exposed surfaces are formed, and thus, the total value of the number of areas divided by imaginary grid lines is set to 100. For example, when the exposed surface is set to a square of 1 mm square, the number of areas divided by imaginary grid lines in one of the exposed surfaces is 4. If exposed surfaces of 1 mm square are formed at 25 locations, the total value of the number of areas divided by imaginary grid lines becomes 100.

[0056] In addition, the number of pattern parts may be 2 or more. In this case, the exposed surface for measurement may be formed in each of the plurality of pattern parts.

[0057] In the case where the pattern portion is very narrow and the number of regions divided by the imaginary grid lines cannot be set to 100, the interval between the imaginary grid lines may be narrowed. For example, the interval between the imaginary grid lines may be changed to a value greater than 0.2 mm and less than 0.5 mm. By narrowing the interval between the imaginary grid lines, the number of regions divided by the imaginary grid lines (i.e., measurement points) can be set to 100 within a very narrow pattern portion.

[0058] When multiple exposed surfaces are formed inside the pattern portion, the distance between these exposed surfaces is reduced as much as possible. Multiple exposed surfaces formed inside the pattern portion may also contact each other. When multiple exposed surfaces are formed inside the non-pattern portion, it is also preferred that the distance between multiple exposed surfaces is reduced as much as possible, and multiple exposed surfaces may also contact each other.

[0059] Furthermore, when measuring the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22, the distance between the exposed surface formed inside the pattern portion and the exposed surface formed inside the non-pattern portion is preferably minimized.

[0060] In the hot-dip coated steel sheet of the present embodiment, a 1 to 5 mm square cross section is exposed at any of the positions of 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip coated layer 2, and when virtual grid lines are drawn at intervals of 0.5 mm in the cross section, a plurality of regions divided by the virtual grid lines are divided into either the first region A1 or the second region A2. Whether the region is divided into the first region A1 or the second region A2 is determined by the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn].

[0061] The first region A1 is set as a region where the ratio (B / A(%)) is greater than 20%. Since the ratio (B / A(%) of the first region A1 is high, the portion of the hot-dip galvanized layer 2 that includes a large amount of the first region appears white or a color close to white when observed with the naked eye or under a microscope. On the other hand, the second region A2 is set as a region where the ratio (B / A(%)) is less than 20%. Since the ratio (B / A(%)) of the second region A2 is low, the portion of the hot-dip galvanized layer that includes a large amount of the second region A2 and a reduced amount of the first region A1 appears to have a metallic luster when observed with the naked eye or under a microscope. Furthermore, the appearance of the portion where the first region A1 and the second region A2 are mixed and the area ratio of the first region A1 is 30 to 70% appears to be pear-skin-like.

[0062] In this way, the surface 2a of the hot-dip galvanized layer 2 appears white or a color close to white, metallic luster, or pear skin-like, depending on the area ratio of the first area A1. Here, in order to visually recognize characters, figures, lines, dots, etc. on the surface 2a of the hot-dip galvanized layer 2, it is sufficient to be able to distinguish the pattern portion 21 constituting these characters, etc. and the non-pattern portion 22 other than these. For this purpose, the area ratio of the first area A1 in the pattern portion 21 and the area ratio of the first area A1 in the non-pattern portion 22 may be different.

[0063] Specifically, the difference between the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22 is preferably 30% or more in absolute value. Thus, the pattern portion 21 and the non-pattern portion 22 become distinguishable. It should be noted that when evaluating the difference in area ratio, it is not necessary to evaluate the entire area of ​​the pattern portion 21 and the non-pattern portion 22. Figure 3As shown in , the area ratio of the first region A1 in the 1 to 5 mm square surface (exposed surface) for measurement provided inside the pattern portion 21 can be regarded as the area ratio of the first region A1 in the entire pattern portion 21. Similarly, the area ratio of the first region A1 in the 1 to 5 mm square surface (exposed surface) for measurement provided inside the non-pattern portion 22 can be regarded as the area ratio of the first region A1 in the entire non-pattern portion 22.

[0064] From the viewpoint of further improving the visual recognizability of the pattern portion 21, the absolute value of the difference between the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22 may be 40% or more, 45% or more, or 50% or more. It is not necessary to set an upper limit on the absolute value of the difference between the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22, but, for example, the absolute value of the difference between the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22 may be set to 95% or less, 90% or less, or 85% or less.

[0065] For example, when the area ratio of the first region A1 in the pattern portion 21 is 75%, the pattern portion 21 appears to be white or a color close to white. In addition, when the area ratio of the first region A1 in the non-pattern portion 22 is 45% or less, it appears to be pear-skin-like or has a metallic luster. Moreover, when the difference in the area ratio of the first region A1 in the pattern portion 21 and the non-pattern portion 22 is 30% or more, the pattern portion 21 and the non-pattern portion 22 can be distinguished by such a difference in appearance.

[0066] In addition, when the area ratio of the first area A1 of the pattern portion 21 is about 65% and the area ratio of the first area A1 of the non-pattern portion 22 is about 35%, both the pattern portion 21 and the non-pattern portion 22 look like pear skin, but since the area ratio of the first area A1 in the pattern portion 21 is large, the pattern portion 21 presents a whiter appearance relative to the non-pattern portion 22. Moreover, when the difference in the area ratio of the first area A1 in the pattern portion 21 and the non-pattern portion 22 is 30% or more, the pattern portion 21 and the non-pattern portion 22 can be distinguished by such a difference in appearance.

[0067] Furthermore, when the first area A1 of the pattern part 21 is 50%, the pattern part 21 looks like a pear skin. In addition, when the area ratio of the first area A1 in the non-pattern part 22 is 20% or less, it looks like a metallic luster. And when the difference in the area ratio of the first area A1 in the pattern part 21 and the non-pattern part 22 is 30% or more, the pattern part 21 and the non-pattern part 22 can be distinguished by such a difference in appearance.

[0068] Thus, if the difference between the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22 is 30% or more in absolute value, the pattern portion 21 and the non-pattern portion 22 have different appearances, and thus the pattern portion 21 can be clearly identified. That is, in the visible light image of the surface 2a of the plating layer 2, since the difference in hue, brightness, chroma, etc. between the pattern portion 21 and the non-pattern portion 22 becomes larger, the pattern portion 21 and the non-pattern portion 22 can be identified.

[0069] On the other hand, if the difference between the area ratio of the first region A1 in the pattern portion 21 and the area ratio of the first region A1 in the non-pattern portion 22 becomes less than 30% in absolute value, the difference in appearance between the pattern portion 21 and the non-pattern portion 22 disappears, and it becomes impossible to clearly identify the pattern portion 21. That is, in the visible light image of the surface 2a of the plating layer 2, since the difference in hue, brightness, chroma, etc. between the pattern portion 21 and the non-pattern portion 22 becomes smaller, it becomes impossible to distinguish the pattern portion 21 from the non-pattern portion 22.

[0070] As described above, an example of the existence ratio of the first area A1 in the pattern portion 21 and the non-pattern portion 22 is shown, but as long as the difference between the area ratio of the first area A1 in the pattern portion 21 and the area ratio of the first area A1 in the non-pattern portion 22 is greater than 30% in absolute value, there is no need to limit the existence ratio of the first area A1 in each of the pattern portion 21 and the non-pattern portion 22.

[0071] The steel plate that serves as the base of the hot-dip coating layer has no particular restrictions on the material. The details will be described below, but as the material, general steel can be used without particular restrictions, and Al-killed steel and some high-alloy steel can also be used, and the shape is not particularly limited. The hot-dip coating layer of this embodiment can be formed by applying the hot-dip coating method described later to the steel plate.

[0072] Next, the chemical composition of the hot-dip coating will be described.

[0073] The hot-dip galvanized layer contains Al: 5-22 mass %, Mg: 1.0-10 mass %, and the balance is Zn and impurities. Preferably, the hot-dip galvanized layer contains Al: 5-22 mass %, Mg: 1.0-10 mass %, and the balance is Zn and impurities.

[0074] Furthermore, the hot-dip coating layer may contain one or two selected from the following Group A and Group B.

[0075] [Group A] Si: 0.0001 to 2 mass%

[0076] [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2% by mass in total

[0077] The content of Al is in the range of 5 to 22 mass % based on the average composition. It is preferable that Al is contained in order to ensure corrosion resistance. If the content of Al in the hot-dip coating is 5 mass % or more, the effect of improving corrosion resistance is further improved. If it is 22 mass % or less, the coating can be stably formed. If it exceeds 22 mass %, the effect of improving corrosion resistance is saturated. From the viewpoint of corrosion resistance, the content of Al is more preferably 6 mass % or more, 8 mass % or more, or 11 mass % or more. From the viewpoint of corrosion resistance, the content of Al is more preferably 20 mass % or less, 19 mass % or less, or 17 mass % or less.

[0078] The content of Mg is in the range of 1.0 to 10% by mass based on the average composition. Mg is preferably contained in order to improve corrosion resistance. If the content of Mg in the hot-dip coating is 1.0% by mass or more, the effect of improving corrosion resistance is further improved. If it exceeds 10% by mass, the dross generation in the coating bath becomes significant, and it becomes difficult to stably manufacture hot-dip coated steel sheets. From the viewpoint of the balance between corrosion resistance and dross generation, the content of Mg is preferably set to 1.5% by mass or more, 2% by mass or more, or 4% by mass or more. From the viewpoint of the balance between corrosion resistance and dross generation, the content of Mg is preferably set to less than 8% by mass, less than 7% by mass, or less than 6% by mass.

[0079] In addition, the hot-dip coating may also contain Si in the range of 0.0001 to 2 mass %. Si may sometimes improve the adhesion of the hot-dip coating, so it may also be contained. Since the effect of improving adhesion is shown by containing more than 0.0001 mass % of Si, it is preferred to contain more than 0.0001 mass % of Si. On the other hand, even if more than 2 mass % is contained, the effect of improving the adhesion of the coating is also saturated, so the content of Si is set to less than 2 mass %. From the viewpoint of coating adhesion, the content of Si is preferably more than 0.0100 mass %, more than 0.0300 mass % or more than 0.1000 mass %. The content of Si may also be set to less than 1 mass %, less than 0.9 mass % or 0.8 mass %.

[0080] The hot-dip coating may contain 0.0001 to 2 mass % of one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in total in an average composition. By containing these elements, the corrosion resistance can be further improved. REM is one or more of the rare earth elements having an atomic number of 57 to 71 in the periodic table.

[0081] The remainder of the chemical composition of the hot-dip coating is zinc and impurities. The impurities include substances other than zinc that are inevitably contained in the base metal and substances that are contained by dissolving the steel in the plating bath.

[0082] It should be noted that the average composition of the hot-dip coating can be measured by the following method. It can be obtained by the following method: first, after removing the surface coating with a coating stripper that does not corrode the coating (for example, NEOREVER SP-751 manufactured by Sancai Chemical Co., Ltd.), the hot-dip coating is dissolved with hydrochloric acid to which an inhibitor (for example, HIBIRON manufactured by SUGIMURA Chemical Industrial Co., Ltd.) is added, and the resulting solution is subjected to inductively coupled plasma (ICP) emission spectrometry analysis. In addition, in the case of not having a surface coating, the removal operation of the surface coating can be omitted.

[0083] Next, the structure of the hot-dip galvanized layer is described. The hot-dip galvanized layer containing Al, Mg and Zn includes [Al phase] and [ternary eutectic structure of Al / Zn / MgZn2]. It has a morphology in which [Al phase] is included in the matrix of [ternary eutectic structure of Al / Zn / MgZn2]. Furthermore, [MgZn2 phase] and [Zn phase] are included in the matrix of [ternary eutectic structure of Al / Zn / MgZn2]. In addition, when Si is added, [Mg2Si phase] may also be included in the matrix of [ternary eutectic structure of Al / Zn / MgZn2].

[0084] Here, [ternary eutectic structure of Al / Zn / MgZn2] refers to the ternary eutectic structure of Al phase, Zn phase and intermetallic compound MgZn2 phase. The Al phase forming the ternary eutectic structure is, for example, equivalent to the "Al" phase at high temperature in the ternary equilibrium state diagram of Al-Zn-Mg (which is an Al solid solution with Zn dissolved in it, containing a small amount of Mg). The Al" phase at high temperature usually separates into fine Al phase and fine Zn phase at room temperature. In addition, the Zn phase in the ternary eutectic structure is a Zn solid solution with a small amount of Al dissolved in it, and depending on the situation, a small amount of Mg further dissolved in it. The MgZn2 phase in the ternary eutectic structure is an intermetallic compound phase existing in the vicinity of Zn: approximately 84 mass % in the binary equilibrium state diagram of Zn-Mg. From the phase diagram, it is believed that no other added elements are dissolved in each phase, or even if they are dissolved, they are only in extremely small amounts. However, since their amounts cannot be clearly distinguished by conventional analysis, the ternary eutectic structure containing these three phases is represented in this specification as [ternary eutectic structure of Al / Zn / MgZn2].

[0085] In addition, [Al phase] refers to a phase that has clear boundaries and appears to be island-shaped in the matrix of the above-mentioned ternary eutectic structure, which is equivalent to the "Al" phase at high temperature in the ternary equilibrium state diagram of Al-Zn-Mg (which is an Al solid solution with solid Zn and contains a small amount of Mg).

[0086] Regarding the Al" phase at high temperature, the amount of Zn and Mg dissolved in the solid solution varies depending on the Al and Mg concentrations of the plating bath. The Al" phase at high temperature is usually separated into a fine Al phase and a fine Zn phase at room temperature, but the island-like shape seen at room temperature can be regarded as retaining the skeleton of the Al" phase at high temperature. From the state diagram, it is believed that no other added elements are dissolved in the phase, or even if they are dissolved, they are extremely small amounts, but since it is impossible to clearly distinguish them through conventional analysis, the phase derived from the Al" phase at high temperature and retaining the skeleton of the Al" phase in shape is referred to as the [Al phase] in this specification. The [Al phase] can be clearly distinguished from the Al phase that forms the ternary eutectic structure mentioned above in microscopic observation.

[0087] In addition, the [Zn phase] refers to a phase that has a clear boundary and appears to be an island in the matrix of the above-mentioned ternary eutectic structure, and in fact, a small amount of Al and a small amount of Mg may also be dissolved. From the state diagram, it is believed that no other added elements are dissolved in this phase, or even if they are dissolved, they are extremely small. This [Zn phase] is a region with an equivalent circle diameter of more than 2.5μm, and can be clearly distinguished from the Zn phase that forms the above-mentioned ternary eutectic structure in microscopic observation.

[0088] In addition, [MgZn2 phase] refers to a phase that has a clear boundary and appears to be an island in the matrix of the above-mentioned ternary eutectic structure, and in fact, a small amount of Al may be dissolved. From the state diagram, it is believed that no other added elements are dissolved in this phase, or even if they are dissolved, they are extremely small. This [MgZn2 phase] can be clearly distinguished from the MgZn2 phase that forms the above-mentioned ternary eutectic structure in microscopic observation. In the coating of the present invention, it is possible that [MgZn2 phase] is not contained depending on the manufacturing conditions, but it will be included in the coating under most manufacturing conditions.

[0089] In addition, [Mg2Si phase] refers to a phase that has a clear boundary and appears to be an island in the solidified structure of the coating when Si is added. From the state diagram, it is believed that there is no solid solution of Zn, Al, or other added elements, or even if solid solution, it is only a very small amount. This [Mg2Si phase] can be clearly distinguished in the coating under microscopic observation.

[0090] Next, the pattern portion, the non-pattern portion, the first region, and the second region in the surface layer of the hot-dip plated layer will be described.

[0091] A pattern portion and a non-pattern portion are formed on the surface of the hot-dip coating of the present embodiment. From the viewpoint of ensuring the beauty of the pattern portion, the pattern portion is preferably configured in a manner that becomes a prescribed shape. In addition, from the viewpoint of ensuring the visual recognizability of the pattern portion, the larger the size of the pattern portion, the more preferred. For example, the pattern portion preferably has an artificial shape. The pattern portion is preferably configured in an intentional shape. The pattern portion is preferably configured in a manner that becomes any one of a straight line portion, a curved line portion, a dot portion, a figure, a number, a symbol or a text, or a shape formed by a combination of two or more of them. For example, on the surface of the hot-dip coating, a text column, a number column, a symbol, a mark, a line graph, a design drawing or a combination thereof formed by the pattern portion is shown. The straight line portion and the curved line portion in the pattern portion are preferably respectively more than 1 mm in length. It can be said that the pattern portion is intentionally formed by showing these shapes. The straight line portion and the curved line portion in the pattern portion preferably have a width that can be identified by visual observation as described later, and are respectively more than 1 mm in length. The dot portion in the pattern portion preferably has an equivalent circle diameter of more than 1 mm and less than 10 mm, and a plurality of dot portions are further preferably arranged regularly. In addition, when the pattern portion is a figure, a number, a symbol, a pattern or a text, it is preferred that these shapes can be visually identified as described later. It can be said that it is further formed intentionally by showing such a size and shape. In addition, the non-pattern portion is an area outside the pattern portion. Even if the shape of the pattern portion is partially missing, as long as it can be identified as a whole, it is also allowed. The non-pattern portion can also be a shape that trims the boundary of the pattern portion.

[0092] When any one of straight line portions, curved line portions, dot portions, graphics, numbers, symbols or characters or a combination of two or more of these is arranged on the surface of the hot-dip galvanized layer, these areas can be used as pattern portions, and the other areas can be used as non-pattern portions. This shape is a shape intentionally or artificially formed by the manufacturing method described later, and is not naturally formed.

[0093] The boundary between the pattern portion and the non-pattern portion can be grasped with the naked eye. The boundary between the pattern portion and the non-pattern portion can also be grasped from an enlarged image obtained using an optical microscope or a magnifying glass.

[0094] The pattern portion is preferably formed to a size that allows the presence of the pattern portion to be discerned with the naked eye, under a magnifying glass or under a microscope. In addition, the non-pattern portion is a region that occupies most of the hot-dip coating layer (the surface of the hot-dip coating layer).

[0095] The pattern portion is arranged in the non-pattern portion. Specifically, the pattern portion is arranged in the non-pattern portion in a manner that it becomes any one of a straight line portion, a curved line portion, a figure, a dot portion, a figure, a number, a symbol or a character, or a shape formed by combining two or more of them. By adjusting the shape of the pattern portion, a straight line portion, a curved line portion, a figure, a dot portion, a figure, a number, a symbol or a character, or a shape formed by combining two or more of them, is shown on the surface of the hot-dip coating. For example, a character column, a number column, a symbol, a mark, a line diagram, a design drawing or a combination thereof formed by the pattern portion is shown on the surface of the hot-dip coating. The shape is a shape intentionally or artificially formed by the manufacturing method described later, and is not naturally formed. As long as a person skilled in the art who knows the appearance of a conventional hot-dip coating can easily distinguish between a pattern portion and a non-pattern portion with an artificial shape.

[0096] It should be noted that, from the viewpoint of improving the visual recognition of the pattern portion, the area ratio of the pattern portion on the surface of the hot-dip galvanized layer is preferably significantly smaller than that of the non-pattern portion. For example, the area ratio of the pattern portion on the surface of the hot-dip galvanized layer is preferably less than 30%, less than 25%, less than 20%, or less than 15%.

[0097] In this way, the pattern portion and the non-pattern portion are regions formed on the surface of the hot-dip galvanized layer, and the pattern portion and the non-pattern portion each include one or two of the first region and the second region.

[0098] Since the first region is a region where the ratio (B / A(%)) is 20% or more, the portion where the first region is more in the hot-dip galvanized layer appears white or a color close to white. On the other hand, since the second region is a region where the ratio (B / A(%)) is less than 20%, the portion where the second region is more in the hot-dip galvanized layer appears to have a metallic luster. In addition, the first region and the second region are dispersedly gathered, and the appearance of the portion where the area ratio of the first region is 30 to 70% appears to be pear-skin-like.

[0099] The first region and the second region are determined as follows. The thickness of the hot-dip galvanized layer is set to t, and the hot-dip galvanized layer is cut in a manner such that a square-shaped exposed surface 3, 4 or 5 parallel to the surface 2a and 1 to 5 mm square in a top view is shown at any position of the 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip galvanized layer. Thus, an exposed surface (cross section) of 1 to 5 mm square parallel to the surface of the hot-dip galvanized layer is formed. Virtual grid lines are drawn at intervals of 0.5 mm in each exposed surface. In the multiple regions divided by the virtual grid lines, the region where the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more is set as the first region, and the region where the ratio (B / A (%)) is less than 20% is set as the second region.

[0100] Hereinafter, a specific method of determining the first area and the second area will be described.

[0101] like Figure 1 and Figure 2 As shown in , the thickness of the hot-dip coating 2 formed on the steel plate 1 is set to t, and an exposed surface 3, 4 or 5 of 1 to 5 mm square parallel to the surface is formed at any position of 3t / 4 position, t / 2 position or t / 4 position from the surface 2a of the hot-dip coating 2. It should be noted that when the pattern part and / or the non-pattern part is so small that a 5 mm square exposed surface cannot be formed inside the pattern part and / or the non-pattern part, the shape of the exposed surface can also be set to a minimum of 1 mm square. In this case, the area of ​​the region for measurement is ensured by increasing the number of exposed surfaces.

[0102] When forming these exposed surfaces 3, 4 or 5, the hot-dip coating is removed by means such as grinding or argon sputtering. In addition, the exposed surface is preferably made into a mirror surface, for example, the maximum height Rz of the exposed surface is preferably set to 0.2μm or less. The exposed surface as the observation object can also be any exposed surface at the 3t / 4 position, t / 2 position or t / 4 position from the surface of the hot-dip coating. The exposed surface at the t / 2 position can also be preferably selected. The B / A ratio obtained in the exposed surface at the t / 2 position is likely to obtain the same value at other positions.

[0103] Then, if Figure 3 As shown in , virtual grid lines were drawn at 0.5 mm intervals on the exposed surface to be observed, and the ratio (B / A (%)) was measured in each of a plurality of regions partitioned by the virtual grid lines.

[0104] A region where the ratio (B / A (%)) is 20% or more is a first region, and a region where the ratio (B / A (%)) is less than 20% is a second region.

[0105] The ratio (B / A(%)) is determined as follows. The plating structure is observed for each area using the secondary electron image of a scanning electron microscope (SEM) to determine the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn]. When determining each phase and structure, elemental analysis based on the energy dispersive X-ray elemental analysis device attached to the SEM is used to confirm the distribution of Zn, Al and Mg. Then, the ratio (B / A(%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is calculated. The [Zn phase] is measured as the area with an equivalent circle diameter of 2.5μm or more. In this way, the Zn phase in the [ternary eutectic structure of Al / MgZn2 / Zn] can be distinguished from the [Zn phase].

[0106] The pattern portion includes a plurality of regions divided by imaginary grid lines, and each region is classified as one of the first region and the second region. In addition, the non-pattern portion also includes a plurality of regions divided by imaginary grid lines, and each region is classified as one of the first region and the second region. That is, the pattern portion may include only one of the first region and the second region, or may include both the first region and the second region. Similarly, the non-pattern portion may include only one of the first region and the second region, or may include both the first region and the second region.

[0107] Here, in the pattern portion, the area ratio of each of the first region and the second region can be obtained. Moreover, when the area fraction of the first region exceeds 70%, the pattern portion looks white or a color close to white. When the area fraction of the first region is 30% to 70%, the pattern portion looks like a pear skin. In addition, when the area fraction of the first region is less than 30%, the pattern portion looks like a metallic luster. In this way, the appearance of the pattern portion depends on the area fraction of the first region.

[0108] On the other hand, in the non-pattern portion, the area ratio of each of the first region and the second region can also be obtained. As with the pattern portion, the appearance of the non-pattern portion depends on the area ratio of the first region.

[0109] Moreover, when the difference between the area ratio of the first area in the pattern part and the area ratio of the first area in the non-pattern part is 30% or more in absolute value, the pattern part and the non-pattern part can be distinguished. When the difference in area ratio is less than 30%, the difference between the area ratio of the first area in the pattern part and the area ratio of the first area in the non-pattern part is small, the appearance of the pattern part and the non-pattern part becomes similar, and it becomes difficult to distinguish the pattern part. The larger the difference in area ratio, the better, more preferably 40% or more, and more preferably 60% or more.

[0110] The pattern portion and the non-pattern portion can be identified by the naked eye, or can be identified by visual observation under a magnifying glass or a microscope. Being able to be identified by visual observation under a magnifying glass or a microscope means, for example, that as long as the shape formed by the pattern portion can be identified by visual observation in a field of view of 50 times or less. Since the pattern portion has an artificially prescribed shape, as long as the field of view is 50 times or less, the pattern portion and the non-pattern portion can be identified by the difference in their appearance. The pattern portion and the non-pattern portion are preferably identifiable at 20 times or less, more preferably 10 times or less, and more preferably 5 times or less.

[0111] The hot-dip plated steel sheet of this embodiment may also have a chemical conversion coating layer or a coating layer on the surface of the hot-dip plated layer. Here, the types of the chemical conversion coating layer or the coating layer are not particularly limited, and known chemical conversion coating layers or coating layers may be used.

[0112] The hot-dip plated steel sheet of the first embodiment of the present invention has been described above. Next, the hot-dip plated steel sheet of the second embodiment of the present invention will be described. The hot-dip plated steel sheet of the second embodiment comprises a steel sheet and a hot-dip plating layer formed on the surface of the steel sheet, the hot-dip plating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass % in average composition, and the remainder contains Zn and impurities, the surface of the hot-dip plating layer contains one or two of the first region and the second region obtained by the following measurement method, and the absolute value of the difference between the area ratio of the first region in the first part, which is an area larger than 1.0 mm square, and the area ratio of the first region in the second part, which is an area larger than 1.0 mm square adjacent to the first part, is 30% or more.

[0113] [Measurement method]

[0114] The thickness of the hot-dip galvanized layer is set to t, and a square cross section of 1 to 5 mm parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position away from the surface of the hot-dip galvanized layer. In each cross section, imaginary grid lines are drawn at intervals of 0.5 mm. In the multiple regions divided by the imaginary grid lines, the region where the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more is set as the first region, and the region where the ratio (B / A (%)) is less than 20% is set as the second region.

[0115] The components of the steel sheet and the hot-dip coating layer of the hot-dip coated steel sheet of the second embodiment are the same as those of the hot-dip coated steel sheet of the first embodiment.

[0116] In the hot-dip plated steel sheet of the second embodiment, the absolute value of the difference between the area ratio of the first area in the first part, which is an area larger than 1.0 mm square, and the area larger than 1.0 mm square adjacent to the first part, which is an area larger than 1.0 mm square, is set to be greater than 30%. Here, "area larger than 1.0 mm square" refers to an area larger than a square of 1.0 mm square. The area that can contain the entirety of the square of 1.0 mm square is the "area larger than 1.0 mm square". According to this feature, the first part and the second part can be clearly identified by the naked eye. By setting the first part and the second part to arbitrary shapes, text, design, etc. can be displayed on the surface of the coating.

[0117] Next, a method for producing the hot-dip plated steel sheet according to the present embodiment will be described.

[0118] In order to manufacture the hot-dip plated steel sheet of the present embodiment by hot-dip plating, the steel sheet is immersed in a hot-dip plating bath with adjusted chemical composition, so that the molten metal adheres to the surface of the steel sheet. Then, the steel sheet is scooped out of the plating bath, and after the amount of adhesion is controlled by gas wiping, the molten metal is solidified. During solidification, although it also varies depending on the composition, the [Al phase] is formed first, and then as the temperature of the molten metal decreases, the [ternary eutectic structure of Al / Zn / MgZn2] is formed. In addition, in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2], the [MgZn2 phase] and the [Zn phase] are formed. Furthermore, when Si is contained in the hot-dip plating layer, the [Mg2Si phase] is formed in the matrix of the [ternary eutectic structure of Al / Zn / MgZn2].

[0119] The inventors of the present invention have recognized that when a coarse [Zn phase] is formed during the solidification of hot-dip coating, the ratio of [Al phase] and [MgZn2 phase] in the hot-dip coating layer increases relatively, and these phases are exposed to the coating surface, so that the appearance of the hot-dip coating layer surface presents an appearance close to white. It is estimated that the formation of [Zn phase] is affected by the number of Zn nucleation points. That is, the inventors of the present invention have recognized that when there are few Zn nucleation points, Zn in the liquid phase before the final solidification will not crystallize as a fine Zn phase in the [ternary eutectic structure of Al / Zn / MgZn2], but will crystallize as a coarse [Zn] phase. As a means of reducing the Zn nucleation points, it is considered to improve the surface cleanliness of the steel plate as the base plate and to reduce the substances that can become Zn nucleation points as much as possible.

[0120] On the other hand, when there are many Zn nucleation sites, the Zn in the liquid phase before the final solidification is crystallized as a fine Zn phase in the [ternary eutectic structure of Al / Zn / MgZn2], and it becomes difficult to crystallize as a coarse [Zn] phase, and the appearance of the hot-dip galvanized layer surface becomes metallic. As a means of increasing the number of Zn nucleation sites, it is considered to arrange substances that can become Zn nucleation sites in a predetermined pattern after improving the surface cleanliness of the steel sheet.

[0121] Next, the manufacturing method of the hot-dip plated steel sheet of the present embodiment is described in more detail. The hot-dip plated steel sheet of the present embodiment is subjected to a treatment to improve the cleanliness of the steel sheet surface, and then the area with low cleanliness is arranged in a predetermined pattern. Then, the steel sheet is dipped in a hot-dip bath, picked up, and then cooled to solidify the hot-dip plated layer, thereby manufacturing.

[0122] Specifically, first, a hot-rolled steel sheet is manufactured, and the hot-rolled sheet is annealed as needed. After pickling, cold rolling is performed to make a cold-rolled sheet. After the cold-rolled sheet is degreased and washed with water, annealing (cold-rolled sheet annealing) is performed, and the annealed cold-rolled sheet is immersed in a hot-dip coating bath to form a hot-dip coating layer. Here, during the period from cold rolling to cold-rolled sheet annealing, in order to improve the surface cleanliness, the steel sheet is subjected to alkaline electrolytic washing, washed with pure water, dried in an inactive atmosphere, and then transferred to the cold-rolled sheet annealing process. Cold-rolled sheet annealing is implemented within 10 seconds from the end of alkaline electrolytic washing. The end of alkaline electrolytic washing is set to the extraction time of the last spray washing of pure water in the alkaline electrolytic washing. Annealing conditions are not particularly limited.

[0123] As a washing liquid for alkaline electrolytic washing, for example, an alkaline washing liquid containing sodium hydroxide or potassium hydroxide is preferably used. As a step of alkaline electrolytic washing, after immersing the steel plate in the washing liquid for immersion washing, the steel plate is electrolytically washed in the washing liquid. Electrolytic washing is preferably alternating electrolytic washing. Then, the attached washing liquid is rinsed off by spraying pure water on the surface of the steel plate. Spray water washing can also be performed by configuring multiple spray nozzles along the forward direction of the steel plate, and spraying pure water from each nozzle. As pure water, water with a resistivity of 1MΩ·cm or more is preferably used.

[0124] It is preferable to remove moisture adhering to the surface of the steel sheet as much as possible by drying in an inert atmosphere during the period from the withdrawal of the spray water washing to the annealing, in order to suppress the adhesion of fine floating particles in the air.

[0125] Organic stains attached to the surface of the steel sheet are removed by alkaline electrolytic washing, and further dried in an inactive atmosphere from the end of the final spray water washing with pure water to before annealing, and then annealing is performed, thereby preventing fine floating particles in the air from adhering to the cold-rolled sheet.

[0126] Next, in order to increase the nucleation sites of Zn, Zn powder is attached to the annealed cold-rolled sheet in a predetermined shape during the period from the annealing of the cold-rolled sheet to the immersion in hot-dip galvanizing. The attachment of Zn powder to the annealed cold-rolled sheet can also be set as follows: Zn powder is attached to a roller in advance in a predetermined shape, and the annealed cold-rolled sheet is transferred when passing through the roller.

[0127] The attached Zn powder will not completely dissolve during hot-dip plating, and will become a nucleation site for Zn during the final solidification of the plating. A portion of the Zn powder diffuses into the plating bath in a solid state. If Zn powder is attached before cold rolling annealing, Zn and the steel sheet will alloy during annealing, hindering the formation of the hot-dip plating layer, so it is not preferred. In addition, when Zn powder is attached after immersion in the hot-dip plating bath, the attached Zn powder will cause the surface appearance of the plating to become rough. The attached Zn powder may be Zn powder containing Zn and impurities. The average particle size of the Zn powder may be, for example, in the range of 4 to 6 μm. The amount of Zn powder attached may be, for example, 1 to 5 g / m 2 As long as the average particle size and the adhesion amount are within this range, the Zn powder can function as a Zn nucleation site.

[0128] Next, the steel sheet is immersed in a hot dip coating bath. The hot dip coating bath contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and Zn and impurities as the remainder. Furthermore, the hot dip coating bath may contain Si: 0.0001 to 2 mass %. In addition, the hot dip coating bath may contain any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in a total amount of 0.0001 to 2 mass %.

[0129] The hot dip coating method is a continuous hot dip coating method in which the steel sheet is continuously passed through a hot dip coating bath.

[0130] The temperature of the hot-dip coating bath varies depending on the composition, but is preferably in the range of, for example, 400 to 500° C. This is because a desired hot-dip coating layer can be formed when the temperature of the hot-dip coating bath is in this range.

[0131] The amount of hot-dip coating can be adjusted by gas wiping or other means on the steel sheet taken out of the hot-dip coating bath. The amount of hot-dip coating is preferably adjusted to a total of 30 to 600 g / m2 on both sides of the steel sheet. 2 When the adhesion is less than 30g / m 2 In the case of the hot dip coated steel sheet, the corrosion resistance is reduced, which is not preferred. 2 In the case of , the molten metal attached to the steel sheet will drip, making it impossible to smooth the surface of the hot-dip coating, which is not preferred.

[0132] After adjusting the amount of hot-dip coating, the steel sheet is cooled. The cooling conditions do not need to be particularly limited. The cooling of the molten metal attached to the steel sheet begins after the steel sheet is scooped out of the hot-dip coating bath. Although it also varies depending on the composition of the hot-dip coating bath, for example, [Al phase] begins to crystallize from around 430°C. Then, [MgZn2 phase] begins to crystallize from around 370°C, [ternary eutectic structure of Al / Zn / MgZn2] crystallizes from around 340°C, and then [Zn phase] crystallizes to complete solidification.

[0133] After the cleanliness of the entire surface of the steel sheet before hot-dip galvanizing is improved, a Zn powder adhesion area serving as a nucleation point of Zn is arranged. In the Zn powder adhesion area, since a large number of Zn nucleation points are contained, Zn or MgZn2 as a eutectic structure is crystallized to form a large amount of [ternary eutectic structure of Al / Zn / MgZn2], while on the other hand, the Zn in the liquid phase is reduced, and the formation of a coarse [Zn phase] is suppressed. As a result, in the Zn powder adhesion area, the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] becomes lower. On the other hand, in an area where no Zn powder is attached and the cleanliness is relatively high, the ratio (B / A (%)) becomes higher.

[0134] The hot-dip plated steel sheet of the present embodiment is capable of distinguishing the pattern portion and the non-pattern portion by setting the absolute value of the difference between the area ratio of the first area in the pattern portion in the first area and the second area and the area ratio of the first area in the non-pattern portion to 30% or more. The pattern portion and the non-pattern portion formed are not formed by printing or painting, so the durability becomes high. In addition, since the pattern portion and the non-pattern portion are not formed by printing or painting, the corrosion resistance of the hot-dip coating is not affected. Furthermore, the pattern portion and the non-pattern portion are not formed by grinding the surface of the hot-dip coating. Therefore, the thickness of the hot-dip coating in the pattern portion is not reduced by the thickness of the coating to the extent of corrosion resistance degradation compared to the thickness of the hot-dip coating in the non-pattern portion. Therefore, the hot-dip plated steel sheet of the present embodiment becomes excellent in corrosion resistance.

[0135] According to the present embodiment, a hot-dip plated steel sheet having high durability of the pattern portion and suitable plating characteristics such as corrosion resistance can be provided. In particular, in the present embodiment, by pressing a roller with Zn powder attached within a range set to a predetermined shape on the annealed cold-rolled sheet with improved cleanliness, and transferring the surface shape of the roller to the annealed cold-rolled sheet, after hot-dip plating, the range of the pattern portion or the non-pattern portion can be made into an intentional or artificial shape on the surface of the hot-dip plated layer, and the pattern portion can be configured in a manner that becomes any one of a straight line portion, a curved line portion, a dot portion, a figure, a number, a symbol or a character, or a combination of two or more of them. Thus, various pattern designs, trademarks, and other identification marks can be expressed on the surface of the hot-dip plated layer without printing, coating, or grinding, and the recognizability and design of the origin of the steel sheet can be improved. In addition, through the pattern portion, the hot-dip plated steel sheet can also be given information required for process management or inventory management, and any information required by the demander.

[0136] This can also contribute to improvement in productivity of hot-dip plated steel sheets.

[0137] Example

[0138] Next, an embodiment of the present invention is described. The cold-rolled steel sheet is subjected to alkaline electrolytic washing, washed with ultrapure water, and then transferred to the annealing process within 10 seconds under an inactive atmosphere. As a washing liquid for alkaline electrolytic washing, an alkaline washing liquid containing sodium hydroxide is set. As a step of alkaline electrolytic washing, the steel sheet is immersed in the washing liquid for immersion washing, and then the steel sheet is electrolytically washed in the washing liquid. The electrolytic washing is set to alternating electrolytic washing. Then, the attached washing liquid is rinsed off by spray washing with ultrapure water. As ultrapure water, water with a resistivity of more than 1MΩ·cm is set. Thereafter, after drying in an inactive atmosphere, the cold-rolled sheet is annealed. The annealing conditions are set as follows: the soaking temperature is 800°C and the soaking time is 1 minute.

[0139] After annealing, Figure 4 Zn powder with an average particle size of 4 to 6 μm is attached to a metal plate having a shape with a grid pattern transferred thereto as shown in the figure. The thickness of the wires constituting the grid pattern is set to 10 mm. The spacing of the center axes of the wires is set to 50 mm. Then, the metal plate is pressed against the annealed steel plate to transfer the Zn powder on the surface of the steel plate, thereby forming Zn nucleation sites locally (in a grid shape with 50 mm intervals). The amount of Zn powder attached is set to 1 to 5 g / m 2 The steel sheet was then dipped into a hot dip coating bath and then picked up. The amount of adhesion was then adjusted by gas wiping and further cooled. In this manner, hot dip coated steel sheets No. 1 to No. 51 shown in Tables 1A to 3B were manufactured.

[0140] However, Zn powder was not attached to some of the steel sheets. The steel sheets without Zn powder were plated using a hot dip bath under the same conditions as No. 1 to 48 to produce hot dip plated steel sheets. A lattice pattern with a spacing of 50 mm was printed on the surface of the hot dip plated layer of the steel sheet by inkjet method. In this way, a Zn-Al-Mg hot dip plated steel sheet No. 52 was produced.

[0141] In addition, the steel sheet without Zn powder was plated with a hot dip bath under the same conditions as No. 1 to 48 to produce a hot dip plated steel sheet. Thereafter, the surface of the hot dip plated layer was ground to form a lattice pattern with a spacing of 50 mm. In this manner, a hot dip plated steel sheet No. 53 was produced.

[0142] For the obtained hot-dip plated steel sheet, the area ratio of the first region and the second region included in the pattern portion and the non-pattern portion is determined. First, the boundary between the pattern portion and the non-pattern portion is determined by observing the surface of the hot-dip plated layer with the naked eye. In the case where it is difficult to determine the boundary with the naked eye, a magnified image of a magnifying glass or an optical microscope is used. In the case where the boundary is difficult to distinguish, the area corresponding to the square pattern on the roller surface is regarded as the pattern portion, and the area ratio of the first region and the second region is evaluated.

[0143] Next, the area ratio of each area contained in the pattern portion and the non-pattern portion is obtained by the measurement method described below. First, the thickness of the hot-dip galvanized layer formed on the steel plate is set to t, and an exposed surface of 5 mm square parallel to the surface is formed at a position t / 2 away from the surface of the hot-dip galvanized layer. However, in the case where t / 2 exceeds 0.2 μm, an exposed surface is formed at a position 0.2 μm away from the surface. At this time, an exposed surface of 5 mm square that is completely contained in the interior of the pattern portion (that is, the entire domain corresponds to the exposed surface of the pattern portion) and an exposed surface of 5 mm square that is completely contained in the interior of the non-pattern portion (that is, the entire domain corresponds to the exposed surface of the non-pattern portion) are formed. When forming the exposed surface, the hot-dip galvanized layer is removed by grinding. In addition, the maximum height Rz of the exposed surface is set to be less than 0.2 μm.

[0144] Next, in the exposed surface to be observed, first, imaginary grid lines were drawn at 0.5 mm intervals on the surface of the hot-dip galvanized layer, and the ratio (B / A (%)) was measured in each of a plurality of regions (0.5 mm square) divided by the imaginary grid lines.

[0145] The determination of the ratio (B / A (%)) is performed as follows. The plating structure is observed for each area using the secondary electron image of a scanning electron microscope (SEM) to determine the [Zn phase] and [ternary eutectic structure of Al / MgZn2 / Zn]. When determining each phase and structure, elemental analysis based on the energy dispersive X-ray elemental analysis device attached to the SEM is used to confirm the distribution of Zn, Al and Mg. That is, the area where Zn is mainly detected among Zn, Al and Mg is regarded as the Zn phase, the area where Al is mainly detected is regarded as the Al phase, and the area where Zn and Mg are mainly detected is regarded as the MgZn2 phase. Based on the distribution of the detected phases, they are classified into [Al phase], [MgZn2 phase], [Zn phase], and [ternary eutectic structure of Al / Zn / MgZn2] according to the above method. Then, the ratio of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] (B / A (%)) is calculated in each of the multiple regions (0.5 mm square) divided by the imaginary grid lines. The [Zn phase] is measured as a region with an equivalent circle diameter of 2.5 μm or more. Thus, the Zn phase in the [ternary eutectic structure of Al / MgZn2 / Zn] is distinguished from the [Zn phase].

[0146] A region where the ratio (B / A (%)) is 20% or more is set as a first region, and a region where the ratio (B / A (%)) is less than 20% is set as a second region.

[0147] Then, the area ratio of the first region in the pattern portion and the area ratio of the first region in the non-pattern portion are obtained. Also, the difference between the area ratio of the first region in the pattern portion and the area ratio of the first region in the non-pattern portion is obtained.

[0148] [Identification]

[0149] The test plates with square pattern parts were visually evaluated based on the following criteria: A, B, and C were considered acceptable in both the initial state and the after-exposure state.

[0150] A: The pattern can be visually recognized from 5m ahead.

[0151] B: The pattern portion cannot be visually recognized from 5 m forward, but visibility is high from 3 m forward.

[0152] C: The pattern portion cannot be visually recognized from 3 m in front, but visibility from 1 m in front is high.

[0153] D: The pattern cannot be visually recognized from 1m ahead.

[0154] [Corrosion resistance]

[0155] The test plate was cut into 150×70 mm and subjected to 30 cycles of the corrosion acceleration test CCT according to JASO-M609. The rusting condition was then investigated and evaluated based on the following criteria. A, B, and C were considered acceptable.

[0156] A: There is no rust, and both the patterned and non-patterned parts maintain a beautiful patterned appearance.

[0157] B: There is no rust, but slight changes in the design appearance are observed in the patterned and non-patterned parts.

[0158] C: The design appearance is slightly impaired, but the pattern portion and the non-pattern portion can be distinguished visually.

[0159] D: The appearance quality of the pattern portion and the non-pattern portion is significantly degraded and cannot be distinguished visually.

[0160] As shown in the table, the Zn-Al-Mg hot-dip plated steel sheets of the present invention examples No. 1 to No. 45 have a chemical composition of the hot-dip plated layer within the range of the present invention, and are hot-dip plated after alkaline electrolytic washing, spray washing with ultrapure water, drying, annealing, and attachment of Zn powder, so that a pattern portion and a non-pattern portion are formed in the hot-dip plated layer, and the absolute value of the difference between the area ratio of the first region in the pattern portion and the area ratio of the first region in the non-pattern portion is 30% or more. As a result, both the recognizability and the corrosion resistance are excellent.

[0161] In the hot-dip plated steel sheet No. 46, since the Al content of the hot-dip plated layer is small, the absolute value of the difference between the area ratio of the first region in the pattern portion and the area ratio of the first region in the non-pattern portion is less than 30%, thereby deteriorating both the visibility and the corrosion resistance.

[0162] In the hot-dip plated steel sheet No. 47, the Al content in the hot-dip plated layer was excessive, so the pattern portion became thinner after 6 months of outdoor exposure, and the visibility was poor.

[0163] The hot-dip plated steel sheet No. 48 had a low Mg content in the hot-dip plated layer, so the pattern portion became thinner after 6 months of outdoor exposure, resulting in poor visibility and reduced corrosion resistance.

[0164] The hot-dip plated steel sheet No. 49 had an excessive Mg content in the hot-dip plated layer, so the visibility and corrosion resistance were inferior.

[0165] Although the composition of the hot-dip coating layer of the hot-dip coated steel sheet No. 50 is appropriate, no Zn powder is attached. Therefore, the absolute value of the difference between the area ratio of the first region in the pattern portion and the area ratio of the first region in the non-pattern portion of the hot-dip coated steel sheet No. 50 becomes less than 30%. As a result, the recognition and corrosion resistance become inferior.

[0166] The composition of the hot-dip coating layer of the hot-dip coated steel sheet No. 51 is appropriate, and Zn powder is attached to the surface of the steel sheet before the hot-dip coating treatment. However, in the hot-dip coated steel sheet No. 51, the surface of the steel sheet before the Zn is attached is not sufficiently cleaned. Therefore, the absolute value of the difference between the area ratio of the first region in the pattern portion and the area ratio of the first region in the non-pattern portion of the hot-dip coated steel sheet No. 51 becomes less than 30%. As a result, the recognition becomes inferior.

[0167] No. 52, in which a square pattern portion was printed by an inkjet method, had its pattern portion thinned due to exposure to the outdoors for 6 months, and visibility decreased.

[0168] In addition, in No. 53 in which a square pattern was formed by grinding, the thickness of the plating layer at the ground portion was reduced, and the corrosion resistance of the ground portion was reduced.

[0169] [Table 1A]

[0170]

[0171] [Table 1B]

[0172]

[0173] The underlined part indicates that it is outside the scope of the present invention.

[0174] [Table 2A]

[0175]

[0176] [Table 2B]

[0177]

[0178] The underlined part indicates that it is outside the scope of the present invention.

[0179] [Table 3A]

[0180]

[0181] [Table 3B]

[0182]

[0183] Explanation of symbols

[0184] 1 Steel Plate

[0185] 2Hot dip coating

[0186] 2a Hot dip galvanized surface

[0187] 21 Pattern Department

[0188] 22 Non-pattern part

[0189] Cross section at 3t / 4 position

[0190] Cross section at 4t / 2 position

[0191] 5 Cross section at 3t / 4 position

[0192] A1 Area 1

[0193] A2 Area 2

Claims

1. A hot-dip galvanized steel sheet, characterized in that: The invention comprises a steel plate and a hot-dip coating layer formed on the surface of the steel plate. The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities in terms of average composition. The hot-dip plated layer has a pattern portion and a non-pattern portion, The pattern portion and the non-pattern portion each include one or two of a first region and a second region obtained by the following measurement method, an absolute value of a difference between an area ratio of the first region in the pattern portion and an area ratio of the first region in the non-pattern portion is 30% or more, [Measurement method] The thickness of the hot-dip galvanized layer is set to t, and a square cross section of 1 to 5 mm parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position away from the surface of the hot-dip galvanized layer. In each of the cross sections, imaginary grid lines are drawn at intervals of 0.5 mm. In the multiple regions divided by the imaginary grid lines, the region where the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more is set as the first region, and the region where the ratio (B / A (%)) is less than 20% is set as the second region.

2. A hot-dip galvanized steel sheet, characterized in that: The invention comprises a steel plate and a hot-dip coating layer formed on the surface of the steel plate. The hot-dip coating layer contains Al: 5 to 22 mass %, Mg: 1.0 to 10 mass %, and the remainder contains Zn and impurities in terms of average composition. further comprising one or two selected from the following Group A and Group B, The hot-dip plated layer has a pattern portion and a non-pattern portion, The pattern portion and the non-pattern portion each include one or two of a first region and a second region obtained by the following measurement method, an absolute value of a difference between an area ratio of the first region in the pattern portion and an area ratio of the first region in the non-pattern portion is 30% or more, [Group A] Si: 0.0001 to 2 mass% [Group B] Any one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C: 0.0001 to 2 mass % in total [Measurement method] The thickness of the hot-dip galvanized layer is set to t, and a square cross section of 1 to 5 mm parallel to the surface is exposed at any position of 3t / 4 position, t / 2 position or t / 4 position away from the surface of the hot-dip galvanized layer. In each of the cross sections, imaginary grid lines are drawn at intervals of 0.5 mm. In the multiple regions divided by the imaginary grid lines, the region where the ratio (B / A (%)) of the area fraction B of the [Zn phase] to the total area fraction A of the [Zn phase] and the [ternary eutectic structure of Al / MgZn2 / Zn] is 20% or more is set as the first region, and the region where the ratio (B / A (%)) is less than 20% is set as the second region.

3. The hot-dip coated steel sheet according to claim 1 or claim 2, characterized in that: The pattern portion is arranged so as to have any one of a straight line portion, a curved line portion, a dot portion, a figure, a number, a symbol, or a character, or a shape formed by combining two or more of them.

4. The hot-dip coated steel sheet according to claim 1 or claim 2, characterized in that: The total amount of hot-dip coating on both sides of the steel plate is 30 to 600 g / m 2 .

5. The hot-dip coated steel sheet according to claim 2, wherein: The hot-dip coating layer has an average composition containing the group A in mass %.

6. The hot-dip coated steel sheet according to claim 2, wherein: The hot-dip coating layer has an average composition containing the B group in mass %.

Citation Information

Patent Citations

  • JP1975043234A

  • Atsudenseijikino seizohoho

    JP1976041899A

  • Game machine

    JP2022094358A

  • High-corrosion-resistance hot-dip galvanized steel plate having highly uniform appearance and manufacturing method therefor

    WO2013002358A1